Public bank lending in times of crisis - Brei, Michael (2013)
This paper studies the role of government-owned banks in the event of financial crises. The study takes an empirical perspective focusing on bank lending. We compare the lending responses across government-owned and private banks to financial crises using the balance sheet information of 764 major banks headquartered in 50 countries over the period of 1994–2009. Using a nested panel regression framework that allows for parameter shifts in the bank lending equation, we find robust evidence that government-owned banks increase their lending during crises relative to normal times, while private banks’ lending decreases. Government-owned banks thus counteract the lending slowdown of private banks. The findings suggest that governments can play an active counter-cyclical role in their banking systems directly through government-owned banks.